Human–AI Collaboration in Academic Writing: Indonesian EFL Students’ Perspectives on AI-Assisted Writing - Febriyanti, Rina Husnaini; Sundari, Hanna; Baron, Rifari; Arfani, Sri; Rahman, Arif (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2026)
The increasing use of artificial intelligence (AI) tools in higher education has changed how students plan, draft, revise, and evaluate academic texts. However, limited research has examined Indonesian EFL undergraduate students’ perspectives on AI adoption in research paper writing. This study investigates students’ perceptions of AI integration in academic writing within the Indonesian EFL context. Employing a case study design, the study involved 77 students from an English Education program at a private university in Jakarta, Indonesia. Data were collected through questionnaires and semi-structured interviews and analysed using descriptive statistics and thematic analysis. The findings indicate that students were highly familiar with AI tools (M = 3.92) and primarily employed them for plagiarism checking (M = 3.95) and sentence recommendations (72.7%). Students also perceived AI as beneficial for improving vocabulary and writing quality (M = 3.90). However, 54.5% of participants expressed concerns that excessive AI reliance could reduce critical thinking skills. The study highlights the importance of integrating AI critically and responsibly in academic writing instruction to support ethical and effective learning practices in higher education.